The Cost of Institutions - Rodriguez, J. author. aut Link
X, 198 p.
Keywords: Contesting prior assumptions that institutions simplify the world for the sake of efficiency, this book argues that rather than institution expansion indicating the movement of markets to optimal states, expanding institutions generate information costs.